2010
DOI: 10.1007/s00280-010-1425-7
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of biweekly S-1 and oxaliplatin combination chemotherapy in metastatic colorectal cancer and pharmacogenetic analysis

Abstract: Biweekly S-1 with oxaliplatin is effective and has improved tolerability and convenience compared to other fluoropyrimidine with oxaliplatin combinations. GSTP1 Ile105Val SNP is associated with treatment outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 27 publications
1
17
1
Order By: Relevance
“…The polymorphism GSTP1 Ile105Val has been predicted to decrease the ability of the cell to defend itself, thus increasing the sensitivity to platinum-based chemotherapy [31,32]. The results of our study showed that GSTP1 105Ile/Val genotype had no significant risk of death when compared with individuals with GSTP1 105Ile/Ile.…”
Section: Discussionsupporting
confidence: 47%
“…The polymorphism GSTP1 Ile105Val has been predicted to decrease the ability of the cell to defend itself, thus increasing the sensitivity to platinum-based chemotherapy [31,32]. The results of our study showed that GSTP1 105Ile/Val genotype had no significant risk of death when compared with individuals with GSTP1 105Ile/Ile.…”
Section: Discussionsupporting
confidence: 47%
“…GSTP1 is a member of the GST superfamily, and is important in the defense function of cells (28). GSTP1 Ile105Val polymorphism leads to a decreased ability in cell defense, thus increasing the sensitivity of an individual to platinum-based chemotherapy (29,30). However, the results of the Cox proportional hazards regression in the present study revealed no significant association between the GSTP1 Ile105Val isoleucine allele, and no homozygous carriers of the valine allele were detected.…”
Section: Discussioncontrasting
confidence: 54%
“…We excluded studies carried out in Asian populations in this discussion as it has been shown that the frequency of GST polymorphisms is different in Asian populations (e.g. dbSNP, http://www.ncbi.nlm.nih.gov/projects/SNP/snp_ref.cgi?rs =1695) [17,[27][28][29]. Three studies reported no overall association and/or did not investigate the association with chemotherapy [12,13,18].…”
Section: Discussionmentioning
confidence: 99%